Deciphering the Involvement of the Epicardium in Cardiac Diseases. - Carmona-Mejías, Rita María; López-Sánchez, Carmen; García-Martínez, Virginio; García-López, Virginio; Muñoz-Chápuli-Oriol, Ramón; Lozano-Velasco, Estefanía; Franco, Diego (MDPI, 2023)
The epicardium is a very dynamic cardiac layer with pivotal contributions during cardiogenesis, acting in the postnatal period as an apparently dormant single-cell layer. In mammalian embryos, the epicardium, which originates form the proepicardium, translocates into the pericardial cavity and subsequently rests on the surface of the myocardium. Later, it gives rise to the epicardiumderived cells, which migrate into subepicardial space, invade the developing myocardium, promoting its growth, and contribute to different cell types. Anomalies in the process of epicardial development, the generation of epicardium-derived cells and their signaling mechanisms in different experimental models lead to defective cardiac development, reminiscent of human congenital heart diseases. Furthermore, recent studies have reported that epicardial derivates in adults, i.e., epicardial adipose tissue, are associated with electrophysiological cardiovascular anomalies. Herein, we provide a state-of-the-art review focusing on both congenital and adult heart diseases associated with epicardial development.
Keywords: Corazón - Enfermedades; Arritmia; Tejido adiposo; Etiología médica; Epicardium; Congenital heart diseases; Arrhythmogenic diseases; Epicardial adipose tissue